Manajemen Pengunjung (Visitor Management) sebagai Pendekatan Pengembangan Kawasan Tamansari Yogyakarta - , mira hafizhah tanjung, M.Sany Roychansyah,ST.,M.Eng.,D.Eng ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Tamansari is an icon of Yogyakarta culture, has been set up by the World Monument Fund (WMF), which has a historical and cultural value is high, also establishes as one of the 100 most endangered cultural sites in the world. Water castle (Tamansari) feature not only because of its location which is in the Keraton Yogyakarta, but also in the beauty of the building. Water Castle (Tamansari) that has the art of European architecture and Java. Because of the beauty of the Water Castle (Tamansari) many tourists that come to see it. The number of visits to the Water Castle (Tamansari) poses a negative impact primarily relates to the attitude and behavior of visitors lacking respect the existence and shield cover sites, , as well as aspects of the physical treatment of buildings is still limited. In addition to the physical damage, began the decline of the quality of visitor visits that can be seen from the visitors who feel the fascination of Water Castle (Tamansari) is declining even not interesting to visit. This research aims to know the perceptions and expectations of visitors to Water Castle (Tamansari) related tourism product development conditions and also conditions of protection,Â as a historical heritage site and knowing the quality of the tourist attraction and quality protection of Water by using the principles of visitor management. The method used was a mix of qualitative and quantitative with gauges perceptions of tourists using IPA (Importance Performance Analysis) using a sample of 100 people solo nusantara and tourists 20 people. The results of this research show that tourists have the perception that some tourism attributes already meet the perceptions and expectations of visitors such as : 1)Pool, 2)Sumur Gemuling, 3)Pulau Cemeti/kenanga, 4)Royal Place Yogyakarta, and 5)Good infrastructure and comfrotable. Whereas attributes do not meet the perceptions and expectations of visitors is: 1)a comfortable road Infrastructures in complex Water Castle (Tamansari). 2)The availability of some alternative mode of transportation to Water Castle (Tamansari), 3)The Centre of the tourist information easy to find and useful to visitors. 4)Regular parking Area, clean and convenient for visitors, 5)Toilet facilities are clean and convenient for visitors and 6) Board the information easy to find, clearly and give important information/useful for visitors. The further of development on tourism attribute less in accordance with the expectations of visitors and to the already fit well preserved and further developed. To minimize the negative impact brought about by visitors need for clear arrangements within the Zoning, the time of the visit, the route and cruising excursions, support services so as to minimize the negative impact.